Draft Annual Plan 1987-88 Volume : VII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1987)
Karbi Anglong and N.C. Hills are the two Hills District of Assapti with a total area of 15222 sq. kms, comprising 19.4% of State area and only with 3.11% of the State population. The density being only 37 in Karbi Anglong and 16 in the N.C. Hills per sq. kms. The population according to 1971 census was 3.79 lakhs in Karbi Anglong and 0.76 lakh in N.C. Hills respectively. The topography is undulating with high steep hills in the N.C. Hills and gentle slopes in the Karbi Anglong District. The altitudes varies from 600 to 900 Metres in Karbi Anglong and from 800 to 1200 Metres in N.C.Hills District. The approximate annual rainfall in Karbi Anglong District is 1266 mm. while it is 2416 mm. in N.C .Hills District.
Government of Assam, Development Commissioner for Hill Areas
Government of Assam, Development Commissioner for Hill Areas